Magnetoresistance of CuCoNi, CuCo and AlFeNi Granular Thin Films Prepared by RF Magnetron Sputtering - Yu, Ong Sing (2002)
In this project, a series of Cu-based and AI-based granular thin films have been prepared using the RF magnetron sputtering system. The effect of the temperature, magnetic field and annealing temperature on the magnetoresisatnce (MR.) of the samples prepared has been discussed. It has been demonstrated that the MR is composition, thickness and temperature dependent. For Cu-based sample which has been prepared under ambient temperature, the highest MR of 1.35% is 'observed for sample CU80.46CO19.54 (CC6). The samples with different compositions of magnetic entities show the different optimum thickness that would give the highest MR. The samples CU72.41CO19.62Ni7.97 and CU75.63CO19.56N4.51 have the maximum MR when the deposition time is 80 minutes whereas for sample CU8O.46CO19.54, the maximum occurs when the deposition is 60 minutes.Upon annealing, the MR of samples also changes. In this study, all of the Cu-based samples prepared at ambient temperature have been annealed at the temperature of 300°C, 350°C, 400°C, 450°C for 10 minutes in the argon environment. Among the samples, CU80.46CO19.54 shows the highest MR of 1.8% when it is annealed at 450°C.